IMPLEMENTASI PROGRAM PERBAIKAN GIZI BALITA DI PUSKESMAS WONOSALAM I KABUPATEN DEM - Dinar Aditya; Hartuti Purnaweni (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Health is a human right and one of the elements of welfare that must be realized in accordance with the 1945 Constitution of the State of the Republic of Indonesia. The government is obliged to set standards and / or criteria on public health, ensure its implementation and facilitate every implementation of these standards and criteria. The nutritional status of children under five is one indicator that describes the level of community welfare. This research will be focused at Puskesmas Wonosalam I Kabupaten Demak. The purpose of this research is to know the implementation of nutrition improvement program of toddlers and the supporting and inhibiting factors in the implementation of the program. This research is a qualitative descriptive research. As informant is head of nutrition section at Demak District Health Office, nutrition practitioner of community health center wonosalam I, village midwife 2 person, village cadre 4 people and mother of toddler 2 people. The research was conducted by interview and observation of the research object. The results showed that in the process of the implementation of nutrition nutrition improvement program, there are 5 precision used. accuracy of policy based on Minister of Health Regulation no. 23 year 2014 article 7 in the form of the implementation of nutrition improvement of children under five through the distribution of PMT and vitamin A, weight monitoring of children under five, posyandu activities and socialization about nutrition of children from two villages have been on target. Second is the accuracy of implementing the nutrition improvement program for children under five from Mranak Village and Getas Village is appropriate and appropriate. Third, the target accuracy has not been achieved seen from the presence of malnourished toddlers in the village of Getas. Fourth is the accuracy of the environment here has not run well seen from the private parties who have not joined the government. The last is the accuracy of the process, the results are correct. Then the supporting factor in this implementation is communication and attitude of executor. Inhibiting factors were found, namely socio-economic conditions and resources. In the end, the government should plan the addition of nutrient in pusosmas wonosala I then allocate funds for the addition of facilities at posyandu in villages brittle, in addition it needs to increase the knowledge of the community about nutrition of toddlers